Regular sound change; The evidence of a single example - Adelaar, Alexander (UI Scholars Hub, 2018)
The Neogrammarians of the Leipzig School introduced the principle that sound changes are regular and that this regularity is without exceptions. At least as a working hypothesis, this principle has remained the basis of the comparative method up to this day. In the first part of this paper, I give a short account of how historical linguists have defended this principle and have dealt with apparent counter evidence. In the second part, I explore if a sound change can be regular if it is attested in one instance only. I conclude that it is, provided that the concomitant phonetic (and phonotactic) evidence supporting it is also based on regularity. If the single instance of a sound change is the result of developments which are all regular in themselves, it is still in line with the regularity principle.